Common Mechanism for Interannual and Decadal Variability in the East African Long Rains. Issue 22 (20th November 2020) - Walker, Dean P.; Marsham, John H.; Birch, Cathryn E.; Scaife, Adam A.; Finney, Declan L.
Abstract: The East African long rains constitute the main crop‐growing season in the region. Interannual predictability of this season is low in comparison to the short rains, and recent decadal drying contrasts with climate projections of a wetter future (the "East African climate paradox"). Here, we show that long rains rainfall totals are strongly correlated with 700 hPa zonal winds across the Congo basin and Gulf of Guinea ( r = 0 . 73 ). Westerly anomalies align with more rainfall, with the same mechanism controlling covariability on interannual and decadal time scales. On both time scales wind anomalies are linked to geopotential anomalies over the Sahel and Sahara, and warming there. Rainfall and wind are significantly correlated with the Madden‐Julian Oscillation (MJO) amplitude, and around 18% of the decadal drying can be explained by MJO amplitude variability. This work shows that predictions of East African rainfall across time scales require robust prediction of both zonal winds and MJO activity. Plain Language Summary: East Africa has two rainfall seasons, the main season, the long rains, runs from March to May. There is currently little understanding of what controls the amount of rainfall during this season. Recent drying, causing many areas to suffer from droughts and food shortages, contrasts with climate projections of a wetter future (the "East African climate paradox"). Rainfall is found to be connected to the strength of easterly winds over the Congo basin and Gulf of Guinea, with the same mechanism controlling variability on both interannual and decadal time scales. From 1998 to 2011 the winds had been getting stronger, with reduced rainfall over East Africa. The cause of the stronger wind is investigated and is partly explained by relatively fast warming in the Sahel than over the Congo, while variation in Madden‐Julian Oscillation (a large‐scale tropical wave) activity, explains around 18% of the decadal drying. Key Points: East African long rains interannual and decadal variability have the same quantitative link to winds across the Congo and Gulf of Guinea Drier long rains and the corresponding zonal wind anomalies are linked to Sahelian warming on both interannual and decadal time scales The Madden‐Julian Oscillation influences both the zonal winds and the long rains on interannual and decadal time scales